IMPLEMENTATION OF LEGAL PRODUCT AGREEMENT PT. ALLIANZ LIFE INDONESIA INSURANCE (SMARTLINK FLEXI ACCOUNT PLUS) - Poetri Enindah Suradinata; Fitriani Fitriani; Zegovia Parera (Musamus University, 2022)
Abstract The aims of this article is to analyze the law of the product agreement